Measurement of fallout radionuclides, 239, 240Pu and 137Cs, in soil and creek sediment: Sydney Basin, Australia. (January 2016) - Smith, B.S.; Child, D.P.; Fierro, D.; Harrison, J.J.; Heijnis, H.; Hotchkis, M.A.C.; Johansen, M.P.; Marx, S.; Payne, T.E.; Zawadzki, A.
Abstract: Soil and sediment samples from the Sydney basin were measured to ascertain fallout radionuclide activity concentrations and atom ratios. Caesium-137 ( 137 Cs) was measured using gamma spectroscopy, and plutonium isotopes ( 239 Pu and 240 Pu) were quantified using accelerator mass spectrometry (AMS). Fallout radionuclide activity concentrations were variable ranging from 0.6 to 26.1 Bq/kg for 137 Cs and 0.02–0.52 Bq/kg for 239+240 Pu. Radionuclides in creek sediment samples were an order of magnitude lower than in soils. 137 Cs and 239+240 Pu activity concentration in soils were well correlated (r 2 = 0.80) although some deviation was observed in samples collected at higher elevations. Soil ratios of 137 Cs/ 239+240 Pu (decay corrected to 1/1/2014) ranged from 11.5 to 52.1 (average = 37.0 ± 12.4) and showed more variability than previous studies. 240 Pu/ 239 Pu atom ratios ranged from 0.117 to 0.165 with an average of 0.146 (±0.013) and an error weighted mean of 0.138 (±0.001). These ratios are lower than a previously reported ratio for Sydney, and lower than the global average. However, these ratios are similar to those reported for other sites within Australia that are located away from former weapons testing sites and indicate that atom ratio measurements from other parts of the world are unlikely to be applicable to the Australian context. Highlights: Comprehensive fallout radionuclide study in the Sydney basin, Australia. Data presented here adds to the single 240 Pu/ 239 Pu atom ratio previously published for Sydney. 240 Pu/ 239 Pu atom ratios support other recent Australian measurements which are lower than published global fallout ratios. 137 Cs/ 239+240 Pu ratios show more variability compared to other studies.